Diagnostic value of combined detection of five biochemical indexes in early diabetic nephropathy - TANG Wei (Linchuang shenzangbing zazhi)
Objective To investigate the diagnostic value of combined detection of serum cystatin C( Cys-C),homocysteine( Hcy),hypersensitive C-reactive protein( hs-CRP),urine β2 microglobulin( U-β2 MG) and urinary albumin( UAlb) in early diabetic nephropathy( DN). Methods From January 2012 to May 2016,48 cases of early DN admitted to our hospital were selected as the observation group,and according to the proportion of 1∶ 1,48 cases of diabetes mellitus( DM) without DN served as control group. In control group,glomerular filtration rate was normal,and color ultrasound examination displayed normal kidney morphology and size. Within 24 h after admission,3 ml fasting venous blood was taken out for detection of serum Cys-C,Hcy,hs-CRP,U-β2 MG and UAlb after centrifugation. U-β2 MG and Cys-C were detected by immune turbidimetry,Hcy by enzymatic method,and hs-CRP and UAlb by immune scattering turbidity method according to the instructions. Results After admission,serum Cys-C [( 1. 16 ± 0. 24) vs.( 0. 93 ±0. 20) mg/L,t = 5. 161],hs-CRP [( 7. 1 ± 2. 9) vs.( 4. 4 ± 2. 7) mg/L,t = 4. 730 ],Hcy [( 22. 20 ±3. 95) vs.( 15. 26 ± 3. 55) mg/L,t = 9. 047],U-β2 MG [( 0. 526 ± 0. 110) vs.( 0. 407 ± 0. 136) mg/L,t = 4. 700] and UAlb [( 42. 8 ± 6. 5) vs.( 10. 4 ± 3. 2) mg/L,t = 31. 022] in the observation group were significantly higher than those in the control group( P < 0. 01 for all). The positive rates of serum Cys-C,hs-CRP,Hcy,U-β2 MG and UAlb in the observation group were 84. 3%,78. 6%,78. 5%,89. 2% and 91. 2%,respectively. The positive rate of combined detection was 100%,and the positive rate was improved by combined detection. Conclusions The serum Cys-C,hs-CRP,Hcy,U-β2 MG and UAlb are sensitive,accurate,simple and reliable indicators of early renal function damage in DM patients. It can be used in early diagnosis of DN,and it is worthy of clinical popularization and application.